Exploration of numerical tafsir ideas on Nadirsyah Hosen's social media - Nuzuliyah, Wilda Rahmatin; Fitri, Annisa (Digital Theory, Culture & Society, 2023)
Social media, usually used as a medium to communicate with each other, has been transformed into a means/container to express Gus Nadir's ideas about the Qur'an and tafsir. This paper aims to examine Gus Nadir's ideas about numerical tafsir, which deviate from his concern about arbitrary interpretations and tend to be mere matchology on social media. An in-depth analysis of his work entitled "Tafsir Al-Qur’an di Medsos: Mengkaji Makna dan Rahasia Ayat Suci Pada Era Media Sosial" will be conducted, but the author limits the object of study only to the sub- theme entitled "Tafsir Otak Atik Angka". This paper is presented using a descriptive method supplemented by reflection, interpretation, criticism, and comparison as analysis needs. It was found that Gus Nadir, a cleric, and legal activist, expressed his frustration in "Tafsir Otak Atik Angka" as a response to the justification of politicians using the Qur'an. Although Gus Nadir emphasizes in-depth study, he does not elaborate on the relationship between the interpretation of numbers and gratuitous interpretation. Nevertheless, his efforts to reveal the model of numerical interpretation according to the method of scholars must be appreciated, even if it is limited to a short writing in cyberspace.